Citrullination Licenses Calpain to Decondense Nuclei in Neutrophil Extracellular Trap Formation - Gößwein, Stefanie; Lindemann, Aylin; Mahajan, Aparna; Maueröder, Christian; Martini, Eva; Patankar, Jay; Schett, Georg; Becker, Christoph; Wirtz, Stefan; Naumann-Bartsch, Nora; Bianchi, Marco E.; Greer, Peter A.; et al. (Frontiers in Immunology, 2019)
Neutrophils respond to various stimuli by decondensing and releasing nuclear chromatin characterized by citrullinated histones as neutrophil extracellular traps (NETs). This achieves pathogen immobilization or initiation of thrombosis, yet the molecular mechanisms of NET formation remain elusive. Peptidyl arginine deiminase-4 (PAD4) achieves protein citrullination and has been intricately linked to NET formation. Here we show that citrullination represents a major regulator of proteolysis in the course of NET formation. Elevated cytosolic calcium levels trigger both peptidylarginine deiminase-4 (PAD4) and calpain activity in neutrophils resulting in nuclear decondensation typical of NETs. Interestingly, PAD4 relies on proteolysis by calpain to achieve efficient nuclear lamina breakdown and chromatin decondensation. Pharmacological or genetic inhibition of PAD4 and calpain strongly inhibit chromatin decondensation of human and murine neutrophils in response to calcium ionophores as well as the proteolysis of nuclear proteins like lamin B1 and high mobility group box protein 1 (HMGB1). Taken together, the concerted action of PAD4 and calpain induces nuclear decondensation in the course of calcium-mediated NET formation.